In vitro degradation and gas production of brachiaria grass with levels of biodiesel byproducts - Juliana Marques Freire; Aderbal Marcos de Azevedo Silva; Heloisa Carneiro; José Morais Pereira Filho; Leilson Bezerra; Denise Cristiane Bidler (Acta Scientiarum. Animal Sciences, 2017)
This study aimed to evaluate the in vitro degradability and gas production in diets containing byproducts from the national biodiesel industry (castor bean, canola, forage radish and black sunflower) replacing Brachiaria grass in four levels (0, 30, 50 and 70%). The inoculum for in vitro incubation was obtained from three fistulated Holstein cows. The experimental design was 4 x 4 factorial completely randomized experimental design consisting of four byproducts and four levels. All byproducts studied had a significant effect (p < 0.05) on in vitro digestibility. The castor bean byproducts promoted the lowest cumulative gas production at the end of 48 hours incubation. Regarding digestibility, the byproducts of canola and radish at 70% level did not affect the degradability of dry matter.